Safety evaluation of changed use levels of the food enzyme triacylglycerol lipase from the non‐genetically modified Limtongozyma cylindracea strain AE‐LAYH (B) - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme triacylglycerol lipase (triacylglycerol acylhydrolase; EC 3.1.1.3) is produced with the non‐genetically modified Limtongozyma cylindracea strain AE‐LAYH (B) by Amano Enzyme Inc. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in six food manufacturing processes. Subsequently, the applicant has requested to revise the use levels for three food manufacturing processes. In this assessment, EFSA updated the dietary exposure assessment of this food enzyme when used in six food manufacturing processes at the revised use levels. As the food enzyme–total organic solids (TOS) are removed from the final foods in one food manufacturing process, the dietary exposure to the food enzyme–TOS was estimated for the remaining five processes. It was calculated to be up to 0.220 mg TOS/kg body weight (bw) per day in European populations. Based on the new data, the revised exposure estimation and the previous evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.